Analysis of inconel 600 oxidized under loss-of-coolant accident conditions: A multi-modal approach. (February 2022) - Copeland-Johnson, Trishelle M.; Nyamekye, Charles K.A.; Ecker, Lynne; Bowler, Nicola; Smith, Emily A.; Rebak, Raul B.; Gill, Simerjeet K.
Abstract: Understanding the performance of cladding materials during a loss-of-coolant accident scenario is crucial for developing next-generation accident tolerant nuclear fuel rod claddings. We describe a multi-modal approach combining synchrotron-based diffraction, and Raman spectroscopy with nano-scale electron microscopy techniques for investigating oxidation of Inconel 600 (A600) in steam and air environments at 1200 °C for 2 h. We report that A600 exposed to steam develops a Cr2 O3 -enriched surface layer while a mixed phase oxide layer containing NiFe2 O4, Cr2 O3, Fe3 O4 and Fe(3–x) Crx O4 is formed in air. Mechanism of oxidation for A600 in air and steam environments is discussed. Graphical Abstract: ga1 Highlights: A600 was exposed to air and steam at 1200 °C for 2 h. Oxidation in steam gave rise to a Cr2 O3 -enriched surface layer. Oxidation in air gave rise to NiFe2 O4 surface layer. Based on extent of oxidation, A600 exhibited superior performance to Zircaloy-2.